Biodiversity of Lecanosticta pine-needle blight pathogens suggests a Mesoamerican Centre of origin - Ariska van der Nest; Michael J. Wingfield; Paulo C. Ortiz; Irene Barnes (IMA Fungus)
Abstract Lecanosticta acicola causes the disease known as brown spot needle blight (BSNB), on Pinus species. The pathogen is thought to have a Central American centre of origin. This was based on the morphological variation between isolates believed to represent L. acicola from native Pinus spp. Two species of Lecanosticta, L. brevispora and L. guatemalensis, have recently been described from Mexico and Guatemala respectively based on morphology and sequence-derived phylogenetic inference. However, the putative native pathogen, L. acicola, was not found in those areas. In this study, the species diversity of a large collection of Lecanosticta isolates from Central America was considered. Phylogenetic analyses of the BT1, ITS, MS204, RPB2 and TEF1 gene regions revealed six species of Lecanosticta, four of which represented undescribed taxa. These are described here as Lecanosticta jani sp. nov. from Guatemala and Nicaragua, L. pharomachri sp. nov. from Guatemala and Honduras, L. tecunumanii sp. nov. from Guatemala and L. variabilis sp. nov. from Guatemala, Honduras, and Mexico. New host and country records were also found for the previously described L. brevispora and L. guatemalensis. Lecanosticta acicola was not found in any of the samples from Central America, and we hypothesize that it could be a northern hemisphere taxon. The high species diversity of Lecanosticta found in Mesoamerica suggests that this is a centre of diversity for the genus.